Screening Amazon rainforest plant extracts for antimicrobial activity: a 15-year commitment to the Brazilian biodiversity - Suffredini, Ivana Barbosa; Silva, Jefferson de Souza; Frana, Sergio Alexandre; Pinto, Katia Cristina; Bento, Keli Cristina Dias; Rudiger, Erika Costa; Belo, Paloma Kelly de Souza; de Arruda, José Rodrigo; Schulze, Juliana Paola; de Castilho, Adriana Lígia; Camargo, Livia Roberta Piedade; Paulino, Ricardo Olivieri; et al. (Frontiers in Antibiotics, 2023)
Introduction The need for new tools to treat infections is constantly growing due to the possibilities of emerging diseases related to environmental changes, climatic catastrophes, microorganism resistance, and human and animal aging, leading to an evident unbalance in the planet’s health. Brazil contains the most significant portion of world biodiversity, a potential source of new antimicrobial natural products. Nonetheless, its environment, particularly its forests, and rainforests, is under threat, meaning that rapidly conducted, comprehensive research into the potential of antimicrobial activity to address this threat is urgently needed. Methods In this study, plants from the Amazon rainforest and the Atlantic forests were collected and tested against several pathogenic microbes relevant to humans, animals, and the environment, and subjected to large-scale susceptibility assays, bioautography, and Artemia salina toxicity assays. From the plants, 2,280 organic and aqueous extracts were obtained from different organs, namely leaves, barks, flowers, fruits, and seeds, and subjected to a large-scale susceptibility screening assay against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Streptococcus mutans, Streptococcus sanguinis, Escherichia coli, Pseudomonas aeruginosa, Candida albicans, Malassezia pachydermatis, Malassezia furfur, and Listeria monocytogenes. Results and discussion The selected extracts were subjected to antimicrobial susceptibility tests to determine their inhibition zone diameters and minimum bactericidal concentrations, to bioautography, and to an Artemia salina toxicity assay, which resulted in 154 active extracts. Moreover, 111 out of 154 extracts were ranked based on scores established by the p-values and the mean rank differences in each set of test results. The final ranking identified which extracts should be studied in further phytochemical research using thin-layer chromatography techniques as a priority. The extracts obtained from plants belonging to Combretaceae, Connaraceae, Convolvulaceae, Fabaceae, Malpighiaceae, Moraceae, Piperaceae, Polygonaceae, and Salicaceae were selected as the most promising ones and used to support the identification of plant-based antimicrobial active compounds from the immense biodiversity of Brazilian forests.